Efektivitas Penggunaan Media Sosial Sebagai Sarana Promosi dan Pemasaran pada UMKM Sablon Anggi Screen di Era Digital - Andina Dwijayanti; Rita Komalasari; Budi Harto; Puji Pramesti; M. Wildan Alfaridzi (IKRA-ITH ABDIMAS, 2023)
This study aims to find out how the use of social media as a means of promotion and marketing forMSMEs Anggi Screen in developing their business in this digital era, which we know where the developmentof digital technology today has provided many conveniences in human life, without exception in shaping theeffectiveness of social media in encouraging promotion and marketing. Promotion and Marketing in sausagemedia usually use online platforms that are often used by the world community. The online platforms used byAnggi screen in its marketing and promotion are Instagram, Whatsapp Business, Youtube, TikTok and marketplaces (lazada, tokopedia, shoope, bukalapak. The research methodology used is a qualitative descriptor tomake descriptions and descriptions systematically, factually and accurately regarding facts and therelationships between their phenomena. With all efforts carried out, it is hoped that it can make promotionand marketing more effective in the use of social media carried out by MSMEs anggi screen, so that inpromotion and marketing it is more cost-effective and can increase sales of MSMEs anggi screen